1990
DOI: 10.23986/afsci.72924
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cell wall degrading enzymes on the preservation of grass and on the silage intake and digestibility in sheep

Abstract: Two experiments were carried out to study the effects of cell wall degrading enzymes as silage additive. A primary growth of timothy was cut with a mower and picked up with a precision-chop forage harvester in Exp. I (early cut), and harvested as direct-cut with a precision-chop harvester in Exp. II (late cut). The additive treatments were in Exp. I: 1) unwilted formic acid (FA) applied as AIV II (4.5 l/t), 2) wilted untreated, 3) wilted FA (4 l/t), 4) wilted enzyme A (glucose oxidase (GO) + hemicellulase (HC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
2
17
1
1
Order By: Relevance
“…In the present study, enzyme treatment resulted in a significant reduction in the apparent digestibility of OM, NDFom and TNSP digestibility in diets DE1 and DE2 relative to the control diet and DE3. Reduced digestibility of enzyme-treated diets has been observed by others in sheep (Jaakola, 1990; and cattle . In these studies, the ADF and NDF contents were lower in the enzyme-treated silages compared to the untreated control; therefore, these authors postulated that the use of enzymes resulted in the breakdown of the more readily degradable fibrous fraction during ensilage, resulting in silage with lower, but less degradable ADF and NDF residues.…”
Section: In Vivo Digestibilities and Nutritive Valuesmentioning
confidence: 76%
“…In the present study, enzyme treatment resulted in a significant reduction in the apparent digestibility of OM, NDFom and TNSP digestibility in diets DE1 and DE2 relative to the control diet and DE3. Reduced digestibility of enzyme-treated diets has been observed by others in sheep (Jaakola, 1990; and cattle . In these studies, the ADF and NDF contents were lower in the enzyme-treated silages compared to the untreated control; therefore, these authors postulated that the use of enzymes resulted in the breakdown of the more readily degradable fibrous fraction during ensilage, resulting in silage with lower, but less degradable ADF and NDF residues.…”
Section: In Vivo Digestibilities and Nutritive Valuesmentioning
confidence: 76%
“…Previous research has reported the e †ects of enzyme application rates, with or without additional LAB, on silage composition (Jaakkola 1990 ;Kung et al 1991 ;Tengerdy et al 1991 ;Selmer-Olsen et al 1993). There is, however, only limited information available on the interaction between enzyme application rates and plant species and their impact on the quality of forages ensiled at high DM levels.…”
Section: Introductionmentioning
confidence: 99%
“…Increases in digestibility 4±9 might indicate that the breakdown of cell wall components could facilitate microbial digestion, while claims have been made that enzymes would principally hydrolyse easily degradable components and leave less digestible organic matter in the treated silages. 10,11 If forages were ef®ciently hydrolysed by cell walldegrading enzymes, then the kinetics of organic matter digestion would be altered. Although several workers examined the effect of enzymes on the in situ degradation of silages, the results were variable and did not reach agreement.…”
Section: Introductionmentioning
confidence: 99%